Quantification of training load in junior provincial rugby union players - Rust, Ruan (Department of Human Biology, 2021)
Study purpose: The objectives of the study were to measure external and internal load and recovery status of junior semi-professional rugby union players (n = 36) during the u/19 Currie Cup campaign. Methods: The monitoring period covered 280 days (July – October) and included phases divided into off-season, pre-season and competition. Twelve league matches were played during the competition phase. The variables associated with external and internal load and recovery status were summarised for each player and also compared to each other to establish relationships between these variables. Data were collected either daily (training load, subjective fatigue and recovery) or weekly (recovery heart rate) or during matches (mechanical load, physiological load and training load). Injuries were also recorded throughout the season. Results: The primary finding of this study was that the players' loads (arbitrary units; AU) (605293 AU), fatigue (4.51.3 AU) and recovery (14.12.3 AU) did not change significantly throughout the different phases of the season. Also, recovery heart remained similar throughout the different phases of the season supporting the pattern of the subjective data. There was no clear predictive relationship between training load, subjective fatigue and recovery prior to sustaining an injury (both soft tissue and musculoskeletal). Conclusion: This study questions the usefulness of a wearable device to measure training load (internal/external), particularly since the session rating of perceived effort(sRPE) is cost effective, quick and easy to implement and provides accurate information. Subjective training load and subjective fatigue did not predict injury in this cohort of players. However, these variables can be used as markers to guide training to ensure the conditioning status of the players remains similar throughout the season. In particular they enable individualised decisions to be made about each player, ensuring that load and fatigue in response to the load remain steady.